(untitled) (Biological Sciences - PJSIR, 2003)
Thieno[2,3-d]pyrimidines (2), (3) and (4) have been obtained via the reaction of 2-amino-4, 5-dimethylthiophen-3- carbonitrile (1) with formamide, acetonitrile and benzonitrile respectively. Treatment of (2), (3) and (4) with chloroacetaldehyde respectively afforded imidazo[1,2-c]thieno[3,2-e]pyrimidines (5), (6) and (7). Anti-microbial activity of the above compounds was determined.